What unites us : reflections on patriotism - Rather, Dan; Kirschner, Elliot (Algonquin Books of Chapel Hill, 2017)
"In a collection of essays, the venerated television journalist celebrates our shared values, reminds us of what matters most in our great country, and shows us what patriotism looks like"--